Economic Warfare and Supply Chain Management: Impacts and Solutions. - Mustapha Laafar; Ahmed Adri; Said Rifai (International Journal of Supply Chain Management, 2020)
In a sharp competition, the global SCM (Supply Chain Management) is based on the globalization of free trade following a liberal principle, which is appropriate to "let the market go" motto and to the removal of government interference. But, the upheavals of the world economy, the hybridization between economic and political sectors, and protectionist ambition. Impact repositories, rationalities, and the forms at management and control of transnational flows. Speaking thus of the economic warfare (EW) "long accepted badly at the ideological level" [1] like mutation or reality already concrete of the international market. In direct opposition with several theories presenting free trade as the most profitable system, among others: The theory of absolute advantage, and the theory of the comparative advantage of A. Smith and Ricardo. The purpose of our article is to propose a Supply Chain Economic Management (SCEM) which takes into account the internal and external environment of the SCM, as well as the forms of the EW, while outlining the possible outcomes of SCM to deal with the impacts of this war.